2022
DOI: 10.1001/jamaneurol.2021.5205
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-Related Imaging Abnormalities and β-Amyloid–Targeting Antibodies

Abstract: IMPORTANCEAfter more than a decade of research and development of clinical trials testing anti-β-amyloid monoclonal antibodies (mAbs), extensive experience has been gained regarding the effects of these treatments in patients with Alzheimer disease (AD). On the verge of an expected large-scale introduction in the clinical setting after the recent US Food and Drug Administration approval of aducanumab, shared knowledge regarding amyloid-related imaging abnormalities (ARIAs) is of paramount importance.OBJECTIVE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
72
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 45 publications
0
72
0
2
Order By: Relevance
“…The exact mechanisms of ARIA-E remain to be fully elucidated. The review of lessons learned from the last decade of research confirmed the ARIA Paradox as the most accredited pathophysiologic model to explain the biological complexity of ARIA-E. 1,4,5,10,12,42 According to this model, ARIA-E is a complex and multifactorial phenomenon resulting from the imbalance between the removal of Aβ deposited in plaques, which is attributed to the dose, time, and type of anti-Aβ (auto) antibodies, and the downstream effects that an excessive mobilization of Aβ can cause on intramural periarterial drainage pathways, 43 which may account for increased transient CAA, cerebrovascular impairment, greater vascular permeability, and an easier extravasation of proteinaceous fluid and VE, particularly in ApoE e4 carriers. 1,2,10,12,[44][45][46] In this proof-of-principle study, we extend the understanding of ARIA-E biology by providing in vivo evidence for an association between ARIA-E and microglial activation through multimodal and multiparametric MRI, CSF testing for anti-Aβ autoantibodies and AT(N) biomarkers, and 11 C-PK11195 PET longitudinal assessments in patients with CAA-ri, a spontaneous human model of the iatrogenic ARIA-E of AD immunotherapy.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The exact mechanisms of ARIA-E remain to be fully elucidated. The review of lessons learned from the last decade of research confirmed the ARIA Paradox as the most accredited pathophysiologic model to explain the biological complexity of ARIA-E. 1,4,5,10,12,42 According to this model, ARIA-E is a complex and multifactorial phenomenon resulting from the imbalance between the removal of Aβ deposited in plaques, which is attributed to the dose, time, and type of anti-Aβ (auto) antibodies, and the downstream effects that an excessive mobilization of Aβ can cause on intramural periarterial drainage pathways, 43 which may account for increased transient CAA, cerebrovascular impairment, greater vascular permeability, and an easier extravasation of proteinaceous fluid and VE, particularly in ApoE e4 carriers. 1,2,10,12,[44][45][46] In this proof-of-principle study, we extend the understanding of ARIA-E biology by providing in vivo evidence for an association between ARIA-E and microglial activation through multimodal and multiparametric MRI, CSF testing for anti-Aβ autoantibodies and AT(N) biomarkers, and 11 C-PK11195 PET longitudinal assessments in patients with CAA-ri, a spontaneous human model of the iatrogenic ARIA-E of AD immunotherapy.…”
Section: Discussionmentioning
confidence: 89%
“…The exact mechanisms of ARIA-E remain to be fully elucidated. The review of lessons learned from the last decade of research confirmed the ARIA Paradox as the most accredited pathophysiologic model to explain the biological complexity of ARIA-E. 1 , 4 , 5 , 10 , 12 , 42 According to this model, ARIA-E is a complex and multifactorial phenomenon resulting from the imbalance between the removal of Aβ deposited in plaques, which is attributed to the dose, time, and type of anti-Aβ (auto)antibodies, and the downstream effects that an excessive mobilization of Aβ can cause on intramural periarterial drainage pathways, 43 which may account for increased transient CAA, cerebrovascular impairment, greater vascular permeability, and an easier extravasation of proteinaceous fluid and VE, particularly in ApoE ε4 carriers. 1 , 2 , 10 , 12 , 44 46 …”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The strong effect of CAA is significant, as anti-Aβ antibody treatments such as aducanumab are not recommended for individuals with CAA due to the high rates of amyloid-related imaging abnormalities (ARIA) [61]. ARIAs are the main adverse event associated with anti-Aβ antibodies and a meta-analysis of clinical trials showed that APOE4 carriers were at the highest risk [62]. Notwithstanding the APOE4-specific pathomechanisms described, persons receiving anti-Aβ antibodies should be genotyped and split into APOE4 carriers and non-carriers.…”
Section: Future Directionsmentioning
confidence: 99%